Utilization of sago starch (Metroxylon asu Rottb.) as substitute for wheat flour in the production of waffle cones - Yamuyam, Norman Jay T. (2010)
Sago starch is now becoming more popular due to its great potential in food and non-food applications. It is one of the many derivatives of the sago palm that grows widely in Southeast Asia. In this product development study, sago starch was used as 75% substitute to wheat flour in the production of waffle cones. In the preliminary trial, Preference Ranking Test and 9-point Hedonic Scale Rating were conducted in order to ascertain the most preferred formulation and to test the acceptability of the final product, respectively. Preference Ranking Test employed 50%, 75% and 100% substitution of sago starch. After the sensory evaluation an statistical anaylsis, it was found out that 75% substitution was the most preferred. Results also revealed that there were no significant differences between the samples at 0.05% level of significance. The final product which was the 75% substitution was then subjected to Consumer Testing using 9-point Hedonic Scale. Results revealed that it is highly acceptable in all attributes at 0.05% level of significance. Rate of sagging and deformation of the waffle cones were also experimented and results revealed that the sago flour substituted waffle cones disintegrated faster than commercial waffle cones since sago starch was very absorbent.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2010
Keywords: Sago; Sago; Sago starch; Starch; Wheat flour; Flour; Substitution; Waffle cones; Proximate analysis; Sago palm; Sago palm -- Southeast Asia; Moisture content